2019
DOI: 10.1073/pnas.1818163116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of chromatin remodeling by Rhp26, a yeast CSB ortholog

Abstract: CSB/ERCC6 belongs to an orphan subfamily of SWI2/SNF2-related chromatin remodelers and plays crucial roles in gene expression, DNA damage repair, and the maintenance of genome integrity. The molecular basis of chromatin remodeling by Cockayne syndrome B protein (CSB) is not well understood. Here we investigate the molecular mechanism of chromatin remodeling by Rhp26, a Schizosaccharomyces pombe CSB ortholog. The molecular basis of chromatin remodeling and nucleosomal epitope recognition by Rhp26 is distinct fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Alternatively, H3K36 methylation may also regulate Rad26 activity, since it has been reported that histone H3 and H4 tails are important for the activity of Rhp26 ( S . pombe Rad26 homolog) in nucleosomes [ 64 ]. Future studies will be required to explore these possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, H3K36 methylation may also regulate Rad26 activity, since it has been reported that histone H3 and H4 tails are important for the activity of Rhp26 ( S . pombe Rad26 homolog) in nucleosomes [ 64 ]. Future studies will be required to explore these possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In the structure, the extended gating helix, which would be incompatible with duplex DNA, appears like a rudder just ahead of where the two DNA strands reanneal. In addition to assisting Pol II, CSB/Rad26 can reposition nucleosomes (22,24,130), raising the possibility that translocation on DNA with an extended gating helix may also occur on the nucleosome.…”
Section: The Gating Helix Is a Remodeler-specific Element Poised To C...mentioning
confidence: 99%
“…2b and 3d ; Supplementary Movie 1 ). Indeed, we previously identified a CSB-specific coupling motif in the CTD (residues 900–910 in Rhp26 and 904–914 in Rad26) that couples the ATPase and chromatin remodeling/translocation activities 37 . The interactions between the newly modeled CTD and HD2-1 linker may explain how this region couples the ATPase and chromatin remodeling/translocation activities.…”
Section: Resultsmentioning
confidence: 99%